ANALYSIS OF FINANCIAL REPORTS TO MEASURE FINANCIAL PERFORMANCE IN THE BINA MANDIRI COOPERATION - Ratih Kusumastuti; Muhsin Muhsin; Surachman Surachman; Dini Martinda Lestari (International Journal of Economy, Education and Entrepreneurship, 2023)
Analysis of cooperative financial performance aims to see the overall financial position of cooperatives, and compare financial performance in individual periods from year to year. This is important because it can provide an overview of the financial health of the cooperative and can also be used as a basis for making decisions in the future. PThis research is a qualitative descriptive research. This method is used to describe or explain phenomena in detail, especially from the point of view of the object under study. In this study, researchers describe how financial reports are used to assess employee performance at the Bina Mandiri Cooperative. Based on the results of the research that has been presented, it can be said that the cooperative's financial performance reports related to staffing for the 2020-2022 financial year are considered very good. The system of voluntary lending by members of cooperatives makes cooperative units run well and can have a positive influence on society in general and members in particular